An ultrasensitive and selective 'turn off' fluorescent sensor with simple operation for the determination of trace copper (II) ions in water and various beverage samples - Elmas, Sukriye Nihan Karuk; Gunay, Ibrahim Berk; Koran, Kenan; Ozen, Furkan; Aydin, Duygu; Arslan, Fatma Nur; Yilmaz, Ibrahim (Taylor & Francis Ltd, 2019)
Considering vital roles of trace copper ions for the health of humans, it is critical to sensitively detect it in foodstuffs. Herein, an ultrasensitive and cost-effective coumarin based fluorescent strategy with a turn-off signal was developed for specific detection of trace Cu2+ ions. Synthesis of 6,7-dihydroxy-3-(3-methylphenyl)coumarin (TMAC) probe was performed and characterized. The developed fluorescent probe presented excellent selectivity. The limit of detection of the sensor can reach as low as 5.13 nM in ACN/H2O (v/v=95/5) buffered by 5 mu M HEPES buffer at pH = 7.0, and it is below the World Health Organization (WHO) guideline for drinking water (31.5 mu M). The probable stoichiometry of TMAC-Cu2+ complex (1:1) was determined by Job's plot method and confirmed by FT-IR and ESI-MS. We further successfully applied TMAC for Cu2+ detection in water and various beverage samples with good recovery (90.24-109.75 %).
Keywords: Coumarin; fluorescence sensor; copper; food samples; beverages